The influence of repeated sprinting on the kinematics of butterfly swimming - Osborough, C.; Peyrebrune, M. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of this study was to determine the effect of repeated sprint performance and fatigue on the kinematics of butterfly swimming. Six experienced national youth male butterfly swimmers undertook a maximal effort repeated sprint test set, during which swimmers were filmed with two under-water and two above water cameras (oblique plane) at 50Hz. The whole body was digitised during a full stroke cycle for each view, with the three-dimensional coordinates being obtained using a DLT algorithm. The results of this study indicate that as swimming speed decreased (i) stroke rate decreased while stroke length remained relatively constant, (ii) hand movement patterns remained similar while changes in elbow angle suggested that the effectiveness of joint flexors and extensors may have been reduced, (iii) the Upsweep, Recovery and Catch appear to the critical stroke phases when swimmers become fatigued.